The sp2-iminosugar glycolipid 1-dodecylsulfonyl-5N, 6O-oxomethylidenenojirimycin (DSO2-ONJ) as selective anti-inflammatory agent by modulation of hemeoxygenase-1 in Bv.2 microglial cells and retinal explants. (January 2018) - Alcalde-Estévez, Elena; Arroba, Ana I.; Sánchez-Fernández, Elena M.; Mellet, Carmen Ortiz; García Fernández, Jose M.; Masgrau, Laura; Valverde, Ángela M.
Abstract: Neuroinflammation is an early event during diabetic retinopathy (DR) that impacts the dynamics of microglia polarization. Gliosis is a hallmark of DR and we have reported the beneficial effects of 1R-DSO-ONJ, a member of the sp 2 -iminosugar glycolipid (sp 2 -IGL) family, in targeting microglia and reducing gliosis in diabetic db/db mice. Herein, we analyzed the effect of DSO2 -ONJ, another family compound incorporating a sulfone group that better mimics the phosphate group of phosphatidylinositol ether lipid analogues (PIAs), in Bv.2 microglial cells treated with bacterial lipopolysaccaride (LPS) and in retinal explants from db/db mice. In addition to decreasing iNOS and inflammasome activation, the anti-inflammatory effect of DSO2 -ONJ was mediated by direct p38α MAPK activation. Computational docking experiments demonstrated that DSO2 -ONJ binds to p38α MAPK at the same site where PIAs and the alkyl phospholipid perifosine activators do, suggesting similar mechanism of action. Moreover, treatment of microglial cells with DSO2 -ONJ increased both heme-oxygenase (HO)-1 and Il10 expression regardless the presence of LPS. In retinal explants from db/db mice, DSO2 -ONJ also induced HO-1 and reduced gliosis. Since IL-10-mediated induction of HO-1 expression is mediated by p38α MAPK activation, our results suggest that this molecular mechanism is involved in the anti-inflammatory effects of DSO2 -ONJ in microglia. Highlights: The sp 2 -iminosugar glycolipid DSO2 -ONJ targets microglial Bv.2 cells and reduced LPS-mediated pro-inflammatory responses. The anti-inflammatory effect of DSO2 -ONJ was mediated by direct p38α MAPK activation. DSO2 -ONJ increased HO-1 and Il10 in retinal explants from db/db mice, which reduced reactive gliosis. Docking experiments are consistent with DSO2 -ONJ binding at a hydrophobic pocket located at the C′-lobe of p38α MAPK. Similar to phosphatidylinositol ether analogues or perifosine, DSO2 -ONJ likely induces autophosphorylation of p38α MAPK.